THE ROLE OF PERSONAL NAMES IN CREATING STEREOTYPICAL ELECTRONIC GAME CHARACTERS - Варбанець, Т. В. (Zapiski z romano-germansʹkoï fìlologìï, 2018)
Over the recent years, electronic games gradually gained strong influence on the psychological development of people, especially the younger generation, and the trend is currently gaining further momentum. They have been little studied, even less so by linguists, which makes the object of the study, linguistic peculiarities of electronic games, highly topical. The subject of this research is the role of personal names that nominate characters in electronic games. Due to the large amounts of information an ordinary human being has to process every moment in life, our mind tends to search for patterns and stereotypes everywhere, including literature, movies, and electronic games. Two types of character classification types were singled out: archetypical and stereotypical. The main types of characters in fantasy setting electronic games (using Witcher 3: The Wild Hunt as the source of material) according to both were enumerated. Afterwards, the peculiarities of nomination of each type was analyzed.